Corrosion properties of bioresorbable FeMn‐Ag alloys prepared by selective laser melting. Issue 10 (25th April 2017) - Wiesener, M.; Peters, K.; Taube, A.; Keller, A.; Hoyer, K.‐P.; Niendorf, T.; Grundmeier, G.
Abstract : FeMn‐Ag alloys as potential bioresorbable implant materials were prepared by selective laser melting (SLM) from mixed powders of FeMn and Ag. The microstructure of the samples is characterized by presence of few micrometers to several tens of micrometer large Ag‐phases within the FeMn matrix. The microstructure dependent corrosion and biomineralization processes in simulated body fluid (SBF) were studied in‐situ by means of electrochemical impedance spectroscopy (EIS). The microstructure and local surface film formation were analyzed by electron microscopy (FE‐SEM) and Raman microscopy. The results clearly show that the Ag‐phase acts as a local cathode within the FeMn matrix. However, surface film formation is observed both for the Ag‐ and the FeMn‐phases, which potentially lowers the self‐corrosion as well as the galvanic coupling of the two phases. The formation of AgCl on the Ag‐phases and mixed metal phosphates on the FeMn‐phases can be observed by local Raman spectroscopic analysis in combination with FE‐SEM characterization. Abstract : FeMn‐Ag alloys as potential bioresorbable implant materials were prepared by selective laser melting of mixed powders of FeMn and Ag. The microstructure dependent corrosion and biomineralization processes in simulated body fluid were studied in‐situ by means of electrochemical impedance spectroscopy. The results clearly show that the Ag‐phase acts as a local cathode within the FeMn matrix.